Effects of accelerated degradation on metal supported thin film-based solid oxide fuel cells. Issue 17 (18th April 2018) - Reolon, R. P.; Sanna, S.; Xu, Y.; Lee, I.; Bergmann, C. P.; Pryds, N.; Esposito, V.
Abstract : Elemental distribution effects are detected throughout the metal supported TF-SOFC, indicating low energy surface elemental interdiffusion and electromigration effects. Abstract : A thin film-based solid oxide fuel cell is deposited on a Ni-based metal porous support by pulsed laser deposition with a multi-scale-graded microstructure design. The fuel cell, around 1 μm in thickness, is composed of a stabilized-zirconia/doped-ceria bi-layered dense electrolyte and nanostructured Ni-stabilized zirconia and La0.6 Sr0.4 CoO3 electrodes as the anode and cathode, respectively. The cell is tested at intermediate temperatures (600–650 °C) with the aim to discern the degradation mechanisms occurring in the cell under accelerated conditions. Under open circuit conditions, electrochemical performances are steady, indicating the stability of the cell. Under electrical load, a progressive degradation is activated. Post-test analysis reveals both mechanical and chemical degradation of the cell. Cracks and delamination of the thin films promote a significant nickel diffusion and new phase formation. Signs of elemental distribution at low temperature are detected throughout the cell, indicating a combination of low energy surface elemental interdiffusion and electromigration effects.